A stretchable spiral fiber material with infrared stealth function
Patent Information
- Application Number
- CN202610542297.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-23
- Publication Date
- 2026-09-25
- Estimated Expiration
- 2046-04-23
AI Technical Summary
这类填料本身较脆,在外部应力作用下难以发生有效变形
[0019]本发明利用同轴湿法纺丝技术制备具有核壳结构的MXene/CA纤维,然后将纤维缠绕在圆棒上,充分拉伸、定型所得,MXene本身具有出色的红外辐射屏蔽性能,赋予纤维红外隐身性能;加入CA与MXene共混纺丝,CA与MXene之间形成氢键网络,借助CA优异的柔韧性显著提升MXene的可纺性与力学强度;将其缠绕在圆棒上,赋予了纤维独特的螺旋结构,使其具有拉伸性,进一步提升其力学性能,同时,材料形成一个空腔,使材料具有一定的隔热性能;本发明所提供的可拉伸螺旋纤维材料能够表现出优异的红外屏蔽特性,实现红外隐身功能,并且能够有效避免热量积聚。
Smart Images

Figure CN122082134B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of infrared stealth materials technology, and relates to a method for preparing a stretchable spiral fiber that can achieve infrared stealth function. Background Technology
[0002] Infrared detection primarily relies on the difference in thermal radiation between the target and the background. Traditional infrared stealth materials mainly consist of metal foils, metal oxide coatings, or metallized films. While these materials possess some infrared reflectivity, their high density and weight make them unsuitable for the urgent need for lightweight modern equipment. The high thermal conductivity of metallic materials leads to rapid heat conduction and may cause heat accumulation at interfaces, which could actually enhance the infrared signal. Furthermore, the rigid structure of metals lacks flexibility and cannot be woven or deformed, making them unsuitable for complex curved surfaces and wearable device applications.
[0003] In recent years, as stealth technology has developed towards "lightweight, flexible, and intelligent" designs, polymer composite materials have played an increasingly important role in the field of novel infrared stealth. This requires the introduction of functional fillers such as carbon-based materials with low infrared emissivity, conductive polymers, and metal nanowires to suppress infrared radiation. These fillers are inherently brittle and difficult to deform effectively under external stress. Uneven filler dispersion can easily lead to localized stress concentration, further weakening the overall material's deformability. When the filler content is low, it is difficult to form a continuous functional network, causing the material's stealth performance to rapidly degrade under strain. How to maintain excellent material deformability and effectively shield infrared signals while achieving high filler loading remains a critical challenge that urgently needs to be addressed.
[0004] Therefore, there is an urgent need to develop a novel infrared stealth fiber material that combines stretchability, weavability, and thermal insulation properties, maintaining stable low infrared radiation characteristics under complex deformation conditions while possessing good mechanical flexibility and thermal management capabilities. The development of flexible infrared stealth fibers can empower aerospace, smart textiles, and emergency rescue fields, becoming a crucial breakthrough for next-generation stealth technology. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides a method for preparing stretchable spiral fibers with infrared stealth function based on MXene. The method forms MXene into spiral fibers, which endows the MXene fibers with stretchability, improves their mechanical properties, and forms cavities. The spiral cavities effectively conduct heat while reducing the thermal conductivity, avoiding local hot spots, and significantly broadening the application scenarios of infrared stealth materials.
[0006] The technical solution adopted in this invention is as follows:
[0007] A method for preparing a stretchable helical fiber material with infrared stealth capabilities includes the following steps:
[0008] Step 1: Add the matrix polymer and MXene to the solvent and disperse and dissolve them thoroughly to prepare core and shell precursor solutions for wet spinning. The total mass fraction of matrix polymer and MXene in the shell precursor solution is 30 wt%, and the ratio of MXene to matrix polymer is 3:2. The total mass fraction of matrix polymer and MXene in the core precursor solution is 17~22 wt%, and the ratio of MXene to matrix polymer is 1:11~2:3.
[0009] The matrix polymer is one or more of cellulose acetate (CA), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), and polyurethane (PU); the solvent is one or more of water, acetone, methanol, isopropanol, ethanol, n-hexane, N,N-dimethylformamide (DMF), and dimethyl sulfoxide (DMSO).
[0010] Step 2: Inject the two precursor solutions into different syringes, use a coaxial needle for wet spinning, and inject the resulting fibers into a coagulation bath to gradually solidify them.
[0011] Step 3: Before the fiber is fully cured, it is wound around a round rod for stretching and shaping to obtain a fiber with a helical structure.
[0012] Preferably, the matrix polymer mentioned in step one is cellulose acetate.
[0013] Preferably, the solvent in step one is dimethyl sulfoxide.
[0014] Preferably, the coagulation bath in step two is one or a combination of water, ethanol, methanol, acetone, and an aqueous solution of ammonium chloride. Preferably, the coagulation bath is an aqueous solution of ammonium chloride, and preferably, the mass fraction of the aqueous solution of ammonium chloride is 5 wt%.
[0015] Preferably, the needles used in step two are 21G / 16G, and the propulsion speed of the core-shell spinning solution is 4ml / h.
[0016] Preferably, the diameter of the round bar mentioned in step three is 4~6mm.
[0017] A stretchable helical fiber material with infrared stealth function is prepared by the above-mentioned method for preparing a stretchable helical fiber material with infrared stealth function.
[0018] The beneficial effects of this invention are:
[0019] This invention utilizes coaxial wet spinning technology to prepare MXene / CA fibers with a core-shell structure. The fibers are then wound onto a round rod, fully stretched, and shaped. MXene itself possesses excellent infrared radiation shielding properties, endowing the fibers with infrared stealth capabilities. The addition of CA and MXene in a co-spinning process creates a hydrogen bond network between CA and MXene. The excellent flexibility of CA significantly enhances the spinnability and mechanical strength of MXene. Winding the fibers onto a round rod imparts a unique helical structure, giving them stretchability and further improving their mechanical properties. Simultaneously, the material forms a cavity, providing a certain degree of thermal insulation. The stretchable helical fiber material provided by this invention exhibits excellent infrared shielding characteristics, achieving infrared stealth functionality, and effectively preventing heat accumulation. Attached Figure Description
[0020] Figure 1 This is a schematic flowchart illustrating a method for preparing a stretchable helical fiber material with infrared stealth function, as provided in an embodiment of the present invention.
[0021] Figure 2 This is a structural schematic diagram of a stretchable helical fiber material with infrared stealth function provided in an embodiment of the present invention.
[0022] Figure 3 The images show SEM (scanning electron microscope) images of MXene / PAN (Mikeene / polyacrylonitrile) fiber in Comparative Example 1, MXene / TPU (Mikeene / thermoplastic polyurethane elastomer) fiber in Comparative Example 2, MXene / PMMA (Mikeene / polymethyl methacrylate) fiber and MXene / CA-8 (8 mm diameter Mikeene / cellulose acetate) fiber in Comparative Example 3.
[0023] Figure 4 The stress-strain curves are shown for the 60@10MCA, 60@20MCA, 60@30MCA, and 60@40MCA helical fibers in Examples 1-4 of this invention.
[0024] Figure 5 For Embodiments 1, 2, 3, and 4 of the present invention, the temperature bars of the thermal platform at 60°C, 60@10MCA, 60@20MCA, 60@30MCA, and 60@40MCA were recorded using an infrared camera. Detailed Implementation
[0025] The present invention will be further described below with reference to specific embodiments. Obviously, the described embodiments are merely preferred embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0026] As attached Figure 1 , 2 As shown, this comparative example provides a method for preparing a stretchable helical fiber with infrared stealth capabilities, which includes the following steps:
[0027] Comparative Example 1 (MXene / PAN fiber)
[0028] Step 1: MXene nanosheets were prepared by etching Ti3AlC2 MAX powder (400 mesh) with LiF / HCl solution, and then MXene powder was prepared using a ball mill. Specific details are as follows:
[0029] 8g of LiF was poured into a polytetrafluoroethylene reaction vessel placed in an ice bath, followed by the addition of 100mL of HCl (9M). The mixture was stirred vigorously for 30 minutes to form a homogeneous hydrofluoric acid solution. Then, 5g of Ti3AlC2 powder was slowly added to the reaction vessel, and the resulting mixed suspension was stirred at 40°C for 42 hours. After the reaction, the resulting mixed suspension was repeatedly washed with deionized water by centrifugation until the pH value was close to 6, yielding etched multilayer Ti3C2TX MXene deposits. The etched MXene suspension was sonicated for 1 hour, then centrifuged at 4000 rpm for 1 hour. The supernatant was collected and freeze-dried to obtain MXene nanosheets. The MXene nanosheets were then ground using a ball mill to obtain MXene nanosheet powder.
[0030] Step 2: Add 2.25g of MXene nanosheet powder and 1.5g of PAN (polyacrylonitrile) to 8.5g of DMSO in sequence, stir well, and prepare a shell precursor solution; add 0.17g of MXene nanosheet powder and 1.5g of PAN to 8.5g of DMSO in sequence, stir well, and prepare a core precursor solution.
[0031] Step 3: Inject the two precursor solutions into two different syringes, and perform wet spinning using a coaxial needle. The resulting fibers are then injected into a coagulation bath prepared with 5 wt% ammonium chloride aqueous solution to coagulate, thus obtaining MXene fibers with a core-shell structure.
[0032] Step 4: The MXene fibers obtained above are wound around a 6mm diameter round rod, fully stretched and shaped to prepare a helical fiber with a core-shell structure.
[0033] Performance testing: such as Figure 3As shown, although PAN possesses flexibility and its –CN groups can form hydrogen bonds with the polar groups on the MXene surface, this is insufficient to impart adequate rigidity to the material. Therefore, when the composite fibers are wound around a round rod and cured, the material struggles to resist deformation and cannot form a proper helical structure.
[0034] Comparative Example 2 (MXene / TPU)
[0035] The difference between this comparative example and Comparative Example 1 is that in step two, 2.25g of MXene nanosheet powder and 1.5g of TPU (thermoplastic polyurethane elastomer) are added to 8.5g of DMSO in sequence and stirred evenly to prepare a shell precursor solution; 0.375g of MXene nanosheet powder and 1.5g of TPU are added to 8.5g of DMSO in sequence and stirred evenly to prepare a core precursor solution.
[0036] Performance testing: such as Figure 3 As shown, TPU is a typical block copolymer, composed of hard crystalline segments and soft elastic segments. Macroscopically, it exhibits excellent high elasticity and shape memory properties. When blended with MXene, although MXene reinforces TPU, TPU still retains its high elasticity and flexibility. When fibers are wound onto a round rod, their molecular chains are forced from a random coiled state with high entropy to an extended and oriented state with lower entropy. After the external force is removed, the molecular chains spontaneously and strongly tend to return to their original state with the highest entropy, exhibiting unwinding behavior and failing to form a stable helical structure.
[0037] Comparative Example 3 (MXene / PMMA)
[0038] The difference between this comparative example and Comparative Example 1 is that in step two, 2.25g of MXene nanosheet powder and 1.5g of PMMA were added to 8.5g of DMSO and stirred evenly to prepare a shell precursor solution; 0.375g of MXene nanosheet powder and 1.5g of PMMA (polymethyl methacrylate) were added to 8.5g of DMSO and stirred evenly to prepare a core precursor solution.
[0039] Performance testing: such as Figure 3 As shown, PMMA is an amorphous, rigid-chain glassy polymer with extremely poor molecular chain mobility. It is mainly composed of non-polar ester groups, while MXene is rich in -OH, -F and other groups on its surface. The two have poor interfacial compatibility. When blended and spun, MXene is prone to agglomeration, which leads to stress concentration and the generation of microcracks. The PMMA matrix does not have the ability to plastically deform to blunt the crack tips, which causes the cracks to destabilize and propagate. As a result, the fibers break brittlely before they are fully wound, and helical fibers cannot be obtained.
[0040] PAN possesses flexibility, but the hydrogen bonds between its –CN chains and the polar groups on the MXene surface are insufficient to improve rigidity. When composite fibers are wound around a round rod and cured, the material struggles to form a proper helix due to its resistance to deformation. TPU, a highly elastic elastomer, retains excellent resilience after blending with MXene; however, once the force is released after the fibers are wound around the rod, they unwind, partially returning to their initial state, thus failing to achieve a stable helix. PMMA itself is brittle, and its flexibility is insufficient after blending and spinning with MXene; the fibers break brittlely before fully winding around the rod, making it impossible to obtain a helical configuration.
[0041] Example 1 (60@10MCA)
[0042] like Figure 1 , Figure 2 As shown, this embodiment provides a method for preparing a stretchable helical fiber with infrared stealth function, which includes the following steps:
[0043] Step 1: MXene nanosheets were prepared by etching Ti3AlC2 MAX powder (400 mesh) with LiF / HCl solution, and then MXene powder was prepared using a ball mill. Specific details are as follows:
[0044] 8g of LiF was poured into a polytetrafluoroethylene reaction vessel placed in an ice bath, followed by the addition of 100mL of HCl (9M). The mixture was stirred vigorously for 30 minutes to form a homogeneous hydrofluoric acid solution. Then, 5g of Ti3AlC2 powder was slowly added to the reaction vessel, and the resulting mixed suspension was stirred at 40°C for 42 hours. After the reaction, the resulting mixed suspension was repeatedly washed with deionized water by centrifugation until the pH value was close to 6, yielding etched multilayer Ti3C2TX MXene deposits. The etched MXene suspension was sonicated for 1 hour, then centrifuged at 4000 rpm for 1 hour. The supernatant was collected and freeze-dried to obtain MXene nanosheets. The MXene nanosheets were then ground using a ball mill to obtain MXene nanosheet powder.
[0045] Step 2: Add 2.25g of MXene nanosheet powder and 1.5g of CA to 8.5g of DMSO in sequence, stir well, and prepare a shell precursor solution; add 0.17g of MXene nanosheet powder and 1.5g of CA to 8.5g of DMSO in sequence, stir well, and prepare a core precursor solution.
[0046] Step 3: Inject the two precursor solutions into two different syringes and perform wet spinning using a coaxial needle. The resulting fibers are injected into a coagulation bath prepared with 5 wt% ammonium chloride aqueous solution and gradually solidified to form MXene fibers with a core-shell structure.
[0047] Step 4: The incompletely cured MXene fibers obtained in the above steps were wound around a 6mm diameter round rod, fully stretched and shaped to prepare a helical fiber with a core-shell structure (numbered 60@10MCA).
[0048] Performance testing: The stretchable MXene spiral fiber material with infrared stealth function prepared in Example 1 was subjected to performance testing. The test results are as follows: the maximum stress of the stretchable MXene spiral fiber material with infrared stealth function is 0.452 MPa, the maximum strain is 1402%, and when it is placed on a 60℃ hot platform, its surface temperature is only 29.5℃, achieving a temperature difference of 30.5℃, which shows that it has good infrared stealth function.
[0049] Example 2 (60@20MCA)
[0050] The difference between this embodiment and Embodiment 1 is as follows: In step two, 2.25g of MXene nanosheet powder and 1.5g of CA are sequentially added to 8.5g of DMSO and stirred until homogeneous to prepare a shell precursor solution; 0.375g of MXene nanosheet powder and 1.5g of CA are sequentially added to 8.5g of DMSO and stirred until homogeneous to prepare a core precursor solution. The final product is a helical fiber with a core-shell structure (designated 60@20MCA).
[0051] Performance testing: The performance of the material prepared in Example 2 was tested, and the results were as follows: the maximum stress of the stretchable MXene spiral fiber material with infrared stealth function was 0.470 MPa, the maximum strain was 1321%, and when it was placed on a 60°C hot platform, its surface temperature was only 27.4°C, achieving a temperature difference of 32.6°C, which shows that it has good infrared stealth function.
[0052] Example 3 (60@30MCA)
[0053] The difference between this embodiment and Embodiment 1 is as follows: In step two, 2.25g of MXene nanosheet powder and 1.5g of CA are sequentially added to 8.5g of DMSO and stirred until homogeneous to prepare a shell precursor solution; 0.64g of MXene nanosheet powder and 1.5g of CA are sequentially added to 8.5g of DMSO and stirred until homogeneous to prepare a core precursor solution. The final product is a helical fiber with a core-shell structure (designated 60@30MCA).
[0054] Performance testing: The stretchable MXene spiral fiber material with infrared stealth function prepared in Example 3 was subjected to performance testing. The test results are as follows: the maximum stress of the stretchable MXene spiral fiber material with infrared stealth function is 0.475 MPa, the maximum strain is 1104%, and when it is placed on a 60℃ hot platform, its surface temperature is only 28.9℃, achieving a temperature difference of 31.1℃, which shows that it has good infrared stealth function.
[0055] Example 4 (60@40MCA)
[0056] The difference between this embodiment and Embodiment 1 is as follows: In step two, 2.25g of MXene nanosheet powder and 1.5g of CA are sequentially added to 8.5g of DMSO and stirred until homogeneous to prepare a shell precursor solution; 1g of MXene nanosheet powder and 1.5g of CA are sequentially added to 8.5g of DMSO and stirred until homogeneous to prepare a core precursor solution. The final product is a helical fiber with a core-shell structure (designated 60@40MCA).
[0057] Performance testing: The stretchable MXene spiral fiber material with infrared stealth function prepared in Example 4 was subjected to performance testing. The test results are as follows: the maximum stress of the stretchable MXene spiral fiber material with infrared stealth function is 0.413 MPa, the maximum strain is 1248%, and when it is placed on a 60℃ hot platform, its surface temperature is only 29.3℃, achieving a temperature difference of 30.7℃, which shows that it has good infrared stealth function.
[0058] Example 5 (60@30MCA-4)
[0059] The difference between this embodiment and Embodiment 1 is as follows: In step two, 2.25g of MXene nanosheet powder and 1.5g of CA are sequentially added to 8.5g of DMSO and stirred until homogeneous to prepare a shell precursor solution; 0.64g of MXene nanosheet powder and 1.5g of CA are sequentially added to 8.5g of DMSO and stirred until homogeneous to prepare a core precursor solution. Furthermore, in step four, the MXene fibers obtained above are wound onto a 4mm diameter rod. The final product is a helical fiber with a core-shell structure (designated 60@30MCA-4).
[0060] Performance testing: The stretchable MXene spiral fiber material with infrared stealth function prepared in Example 5 was subjected to performance testing. The test results are as follows: the maximum stress of the stretchable MXene spiral fiber material with infrared stealth function is 0.56 MPa, the maximum strain is 138%, and when it is placed on an 80℃ hot platform, its surface temperature is only 44.1℃, achieving a temperature difference of 40.9℃, which shows that it has good infrared stealth function.
[0061] Example 6 (60@30MCA-5)
[0062] The difference between this embodiment and Embodiment 1 is as follows: In step two, 2.25g of MXene nanosheet powder and 1.5g of CA are sequentially added to 8.5g of DMSO and stirred until homogeneous to prepare a shell precursor solution; 0.64g of MXene nanosheet powder and 1.5g of CA are sequentially added to 8.5g of DMSO and stirred until homogeneous to prepare a core precursor solution. Furthermore, in step four, the obtained MXene fibers are wound onto a 5mm diameter rod. The final product is a helical fiber with a core-shell structure (designated 60@30MCA-5).
[0063] Performance testing: The stretchable MXene spiral fiber material with infrared stealth function prepared in Example 6 was subjected to performance testing. The test results are as follows: the maximum stress of the stretchable MXene spiral fiber material with infrared stealth function is 0.26 MPa, the maximum strain is 134%, and when it is placed on an 80℃ hot platform, its surface temperature is only 41.3℃, achieving a temperature difference of 38.7℃, which shows that it has good infrared stealth function.
[0064] Example 7 (60@30MCA-8)
[0065] The difference between this embodiment and Embodiment 1 is as follows: In step two, 2.25g of MXene nanosheet powder and 1.5g of CA are sequentially added to 8.5g of DMSO and stirred until homogeneous to prepare a shell precursor solution; 0.64g of MXene nanosheet powder and 1.5g of CA are sequentially added to 8.5g of DMSO and stirred until homogeneous to prepare a core precursor solution. Furthermore, in step four, the MXene fibers obtained above are wound onto a cylindrical rod with a diameter of 8mm. The final product is a helical fiber with a core-shell structure (designated 60@30MCA-8).
[0066] Performance testing: The stretchable MXene helical fiber material with infrared stealth function prepared in Example 7 was subjected to performance testing, and the test results are as follows: Figure 3 As shown, when the winding diameter increases to 8 mm, the fiber curvature is small, resulting in an insignificant stress difference and stress gradient between the inner and outer sides. This makes it difficult for the fiber to be 'locked' into a stable helical structure during the drying process. Because it fails to fully adapt to bending deformation, the internal stress relaxation is uneven, ultimately leading to some areas rebounding or deforming, and a stable helical structure cannot be obtained.
[0067] Effect verification:
[0068] I. The helical fibers obtained in Examples 1-4 above were subjected to tensile property tests, and the test results are as follows: Figure 4 As shown, the maximum stress of 60@10MCA is 0.452MPa and the maximum strain is 1402%. With the increase of MXene content and the decrease of CA content in the shell, the stress increases, with the maximum stress of 60@20MCA being 0.470MPa and the maximum stress of 60@30MCA being 0.475MPa. With the continued increase of MXene content and the continued decrease of CA content in the shell, the stress and strain of the helical fiber decrease, with the maximum stress of 60@40MCA being 0.413MPa and the maximum strain being 1104%.
[0069] II. The helical fibers obtained in Examples 1-4 above were subjected to infrared stealth performance testing, and the test results are as follows: Figure 5
[0070] As shown in Figure 3, there is a large temperature difference between the spiral fiber and the thermal platform. The MXene / CA spiral fibers prepared using the above method all have good infrared stealth capabilities.
[0071] In the above embodiments, CA and MXene were blended and prepared using coaxial wet spinning technology to produce MXene / CA fibers, resulting in a stretchable helical fiber material with infrared stealth capabilities. CA is a polymer with excellent fiber-forming properties and flexible molecular chains. In the spinning solution, it can form an entangled network, effectively transferring and dispersing stress. Its toughness improves the processability and brittleness of MXene, greatly enhancing the spinnability of the blend and improving the mechanical properties of the MXene fibers. The MXene / CA fibers are wound and stretched along a round rod to form a helical fiber. The helical structure further enhances the mechanical properties of the material and imparts stretchability to the fiber. Due to the low infrared emissivity of MXene itself and the cavities formed by the helical structure, it has a certain heat insulation effect, giving the MXene / CA fiber infrared stealth capabilities.
[0072] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A method for preparing a stretchable helical fiber material with infrared stealth function, characterized in that, The method includes the following steps: Step 1: Add the matrix polymer and MXene to the solvent and disperse and dissolve them thoroughly to prepare core and shell precursor solutions for wet spinning. The total mass fraction of matrix polymer and MXene in the shell precursor solution is 30 wt%, and the mass ratio of MXene to matrix polymer is 3:
2. The total mass fraction of matrix polymer and MXene in the core precursor solution is 17~22 wt%, and the mass ratio of MXene to matrix polymer is 1:11~2:
3. The matrix polymer is one or more of cellulose acetate, polyacrylonitrile, polymethyl methacrylate, and polyurethane; the solvent is one or more of water, acetone, methanol, isopropanol, ethanol, n-hexane, N,N-dimethylformamide, and dimethyl sulfoxide. Step 2: Inject the two precursor solutions into different syringes, use a coaxial needle for wet spinning, and inject the resulting fibers into a coagulation bath to gradually solidify them. Step 3: Before the fiber is fully cured, it is wound around a round rod for stretching and shaping to obtain a fiber with a helical structure.
2. The method for preparing the stretchable helical fiber material with infrared stealth function according to claim 1, characterized in that, The matrix polymer mentioned in step one is cellulose acetate.
3. The method for preparing the stretchable helical fiber material with infrared stealth function according to claim 1, characterized in that, The solvent mentioned in step one is dimethyl sulfoxide.
4. The method for preparing the stretchable helical fiber material with infrared stealth function according to claim 1, characterized in that, The coagulation bath mentioned in step two is one or a combination of water, ethanol, methanol, acetone, and an aqueous solution of ammonium chloride.
5. The method for preparing the stretchable helical fiber material with infrared stealth function according to claim 4, characterized in that, The coagulation bath is an aqueous solution of ammonium chloride.
6. The method for preparing the stretchable helical fiber material with infrared stealth function according to claim 5, characterized in that, The mass fraction of the ammonium chloride aqueous solution is 5 wt%.
7. The method for preparing the stretchable helical fiber material with infrared stealth function according to claim 1, characterized in that, The coaxial needle specifications mentioned in step two are 21G / 16G, and the propulsion speed of the core-shell spinning solution is 4mL / h.
8. The method for preparing the stretchable helical fiber material with infrared stealth function according to claim 1, characterized in that, The diameter of the round bar mentioned in step three is 4~6mm.
9. A stretchable helical fiber material with infrared stealth function prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Functionalization polyacrylonitrile resin, production and application of the same in fibre
CN101153068A
Core-shell structure fiber based on carbon nano material and preparation method thereof
CN107177892A